Clinician assessment tools for patients with diabetic foot disease: A systematic review - Fernández Torres, Raúl; Ruiz-Muñoz, María; Pérez Panero, Alberto José; García-Romero, Jerónimo; González-Sánchez, Manuel (Multidisciplinary Digital Publishing Institute (MDPI), 2020)
The amputation rate in patients with diabetes is 15 to 40 times higher than in patients without diabetes. To avoid major complications, the identification of high-risk in patients with diabetes through early assessment highlights as a crucial action. Clinician assessment tools are scales in which clinical examiners are specifically trained to make a correct judgment based on patient outcomes that helps to identify at-risk patients and monitor the intervention. The aim of this study is to carry out a systematic review of valid and reliable Clinician assessment tools for measuring diabetic foot disease-related variables and analysing their psychometric properties. The databases used were PubMed, Scopus, SciELO, CINAHL, Cochrane, PEDro, and EMBASE. The search terms used were foot, ankle, diabetes, diabetic foot, assessment, tools, instruments, score, scale, validity, and reliability. The results showed 29 validated studies with 39 Clinician assessment tools and six variables. There is limited evidence on all of the psychometric characteristics of the Clinician assessment tools included in this review, although some instruments have been shown to be valid and reliable for the assessment of diabetic neuropathy (Utah Early Neuropathy Scale or UENS); ulceration risk (Queensland High Risk Foot Form or QHRFF); diabetic foot ulcer assessment, scoring, and amputation risk (Perfusion, extent, depth, infection and sensation scale or PEDIS and Site, Ischemia, Neuropathy, Bacterial Infection, and Depth score or SINBAD); and diabetic foot ulcer measurement (Leg Ulcer Measurement Tool LUMT). © 2020 by the authors. Licensee MDPI, Basel, Switzerland.
Keywords: Diabetes - Complicaciones y secuelas; Diabetes; Diabetes complications; Ulcer; Outcome measures; Evidence